Update of Radiofrequency Ablation for Treating Benign and Malignant Thyroid Nodules. The Future Is Now - Tufano, Ralph P.; Pace-Asciak, Pia; Russell, Jonathon O.; Suárez, Carlos; Randolph, Gregory W.; López, Fernando; Shaha, Ashok R.; Mäkitie, Antti; Rodrigo, Juan P.; Kowalski, Luiz Paulo; Zafereo, Mark; Angelos, Peter; et al. (Frontiers in Endocrinology, 2021)
New technologies are available to safely ablate thyroid nodules without removal of the gland itself. Laser Ablation (LA) and Radiofrequency ablation (RFA) are the most widely used thermal ablative treatments for solid nodules. High-Intensity Focused Ultrasound (HIFU) as well as Microwave Ablation (MA) are two other modalities that fall under the umbrella of thermal ablative techniques and are gaining traction as longer-term data emerges (104,105). Although, chemical ablation via percutaneous ethanol injection is cheaper and requires less costly equipment, it is considered the treatment of choice for cystic nodules and it tends to be less effective for solid nodules (3-5). Each minimally invasive technique has its subtle differences and nuances, but they all share ease of use, effectiveness and safety.